STRATEGIC COMMERCIAL MANAGEMENT - LOWE, DAVID (ROUTLEDGE, 2026)
Commercial acumen is a critical skill that underpins the realisation of successful and high-value trading relationships.This concise textbook provides knowledge of the principles of strategic commercial management together with a framework for critically understanding commercial practice within and between organisations. It also examines relevant commercial management best practice and aids the development of the intellectual skills to communicate the rationale behind the strategic commercial decisions made by organisations. Across each chapter, it presents practical and transferable skills for designing, negotiating, awarding and managing B2B transactions.Strategic Commercial Management provides a practical and concise introduction for executive education students currently studying for MSc and MBA apprenticeship programmes, as well as supplementary reading for postgraduate students studying Strategic and Commercial Management.
Keywords: Industrial management.; Strategic planning.; elektronické knihy; electronic books